HUBUNGAN ANTARA BELAJAR BERDASAR REGULASI DIRI DENGAN SIKAP TERHADAP EKSTRAKURIKULER PADA SISWA KELAS XI SMA MARDISISWA SEMARANG - Randwitya Ayu Ganis Hemasti (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2019)
This study aimed to determine the relationship between learning based on self-regulation with attitudes toward extracurricular activities, and to determine the effective contribution of learning based on self-regulation. The population in accordance with the characteristics in this study amounted to 113 students in Mardisiswa Semarang High School. Data collection uses a scale of learning based on self-regulation consisting of 31 items (α = 0.939), and a scale of attitude towards extracurricular consisting of 30 items (α = 0.970). The results of hypothesis testing show that learning based on self-regulation is positively related to attitudes towards extracurricular activities indicated by rxy = 0.529 with a significance level of correlation of 0,000 (p <0.05). The test results obtained coefficient of determination of 0, 280. It means that learning based on student self-regulation gives an effect of 28% on attitudes toward extracurricular. While 72% of attitudes towards extracurricular are influenced by other factors outside the variables of this study. These factors include personal experience, the influence of others who are considered important, the influence of culture, mass media, religious institutions, and the influence of emotional factors. Keywords: self-regulation, Extracurricular. Penelitian ini ditujukan untuk mengetahui hubungan antara belajar berdasar regulasi diri dengan sikap terhadap ekstrakurikuler, dan untuk mengetahui sumbangan efektif belajar berdasar regulasi diri. Populasi yang sesuai dengan karakteristik dalam penelitian ini berjumlah 113 siswa di SMA Mardisiswa Semarang. Pengumpulan data menggunakan skala belajar berdasar regulasi diri yang terdiri dari 31 item (α = 0,939), dan skala sikap terhadap ekstrakurikuler yang terdiri dari 30 item (α = 0,970).Hasil pengujian hipotesis menunjukkan bahwa belajar berdasar regulasi diri berhubungan secara positif dengan sikap terhadap ekstrakurikuler yang ditunjukkan dengan rxy= 0,529 dengan tingkat signifikansi korelasi sebesar 0,000 (p<0,05). Hasil pengujian diperoleh nilai koefisiensi determinasi sebesar 0, 280. Artinya adalah belajar berdasar regulasi diri siswa memberikan pengaruh sebesar 28% terhadap sikap terhadap ekstrakurikuler. Sedangkan 72% sikap terhadap ekstrakurikuler dipengaruhi oleh faktor-faktor lain di luar variabel penelitian ini. Faktor- faktor tersebut antara lain adalah pengalaman pribadi, pengaruh orang lain yang dianggap penting, pengaruh kebudayaan, media massa, lembaga agama, dan pengaruh faktor emosional Kata kunci: Regulasi Diri, Ekstrakurikuler